Use of Quantum Well Embedded in a P-Type Layer to Enhance the Efficiency of PN-Junction Solar Cells - ขันเงิน สมพร; ชิณวงศ์ สุริยา; เสาวดี นาท; บุรินทร์ประโคน ธนูสิทธิ์ (KKU Science Journal, 2014)
Effect of structural parameters such as well-width, potential energy depth and volume fraction of quantum wells embedded in a p-type semiconductor on the recombination rates of electron and hole has been investigated. Electron wave functions are obtained by the shooting method. The overlap integral of electron and hole is calculated. The recombination rate is proportional to the square of the overlap integral of electron and hole. The results show that the recombination rate in the structure of symmetric quantum wells embedded in a p-type semiconductor decreases significantly. For the structure which has the volume fraction less than 5%, the recombination rate decreases while the well width and the potential energy depth increase. In addition, the results state that the structure with appropriate structural parameters of the quantum wells can reduces the recombination rate up to 65%.